1982
DOI: 10.1002/jmv.1890090208
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay detection of igm antibodies to the hbv‐associated delta (δ) antigen: Clinical significance in δ infection

Abstract: A sensitive radioimmunoassay was developed for specific detection of IgM antibodies to the hepatitis b virus-associated delta antigen. The test is based on the selective absorption of IgM by anti-IgM fixed on a solid phase. Transient primary IgM anti-delta responses with no conversion to a secondary IgG response were observed in acute self-limited delta infection. IgM anti-delta was invariably found in hepatitis B surface antigen (HBsAg) carriers with active delta infection and liver disease, while it was abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(53 citation statements)
references
References 15 publications
(2 reference statements)
2
48
1
2
Order By: Relevance
“…IgM anti-HD was measured using a previously described capture immunoassay. 16 Serum samples were tested for HDV RNA as previously reported 17 by semiquantitative single and nested polymerase chain reaction (PCR) assays, with a sensitivity of approximately 1,000 and 1-10 genomes/mL respectively. Serum HBV DNA levels were determined with a commercial quantitative PCR assay (Amplicor HBV Monitor Test, Roche Diagnostics, GmbH Mannheim, Germany) with a sensitivity threshold of about 400 copies/mL.…”
Section: Methodsmentioning
confidence: 99%
“…IgM anti-HD was measured using a previously described capture immunoassay. 16 Serum samples were tested for HDV RNA as previously reported 17 by semiquantitative single and nested polymerase chain reaction (PCR) assays, with a sensitivity of approximately 1,000 and 1-10 genomes/mL respectively. Serum HBV DNA levels were determined with a commercial quantitative PCR assay (Amplicor HBV Monitor Test, Roche Diagnostics, GmbH Mannheim, Germany) with a sensitivity threshold of about 400 copies/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies have indicated that HBV carriers superinfected with HDV generally develop and maintain serologic markers that indicate ongoing viral replication, including high titers of anti-HD and persistence of IgM anti-HD, serum HDV RNA, and intrahepatic HDAg (22,64,187,188,190). However, this is not always the case, and patients may lose detectable HBsAg secondary to HDV suppression of HBV replication (46,91,110,135).…”
Section: Virus-encoded Proteinsmentioning
confidence: 77%
“…However, the diagnosis rests on finding HDAg in the liver or, in those patients with active viral replication, finding HDV RNA in serum (64,188,190).…”
Section: Methods Of Detecting Hdvmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Linkers play an important role in displaying the epitopes on surface of fusion proteins. 39 We used Glycine and Serine (GS 4 ) 3 residues from flexible linkers that could separate different domains in chimeric proteins and they have sufficient flexibility that may enhance protein expression level. 40 Then chimeric VP8-S2 gene was constructed, it was cloned and sub-cloned into pGH and pET32a(+), respectively.…”
Section: Protein Expression and Purification Analysesmentioning
confidence: 99%